Oko Mama sebagai Alat Konsolidasi Politik pada Masyarakat (ATOIN PAH METO): (Studi Tentang Pemilihan Kepala Desa Tahun 2023 di Desa Saenam, Kecamatan Miomaffo Barat, Kabupaten Timur Tengah Utara) - Luisa Adonia Bamae; Esrah D.N.A. Benu; Diana S. Tabun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research is entitled Oko Mama as a Tool of Political Consolidation in Society (Atoin Pah Meto) (Case Study of the 2023 Village Head Election in Saenam Village, West Miomaffo District, TTU). The main problem of this research is how oko mama as a tool of political consolidation in the village head election in Saenam Village, in establishing relations between candidates and the community in the village head election in Saenam Village, West Miomaffo District, TTU. The theory used in this study is the theory of political consolidation which refers to oko mama as a tool of political consolidation in Society (Atoin Pah Meto). The results of this study indicate that Oko Mama has several functions, namely as a cultural, as a form of appreciation to guests to convey a purpose, where oko mama is a tool for political consolidation ahead of the village head elections. However, in this study, oko mama does not provide a certainty for the community to choose the candidate due to several factors including educational factors and the community's perception of the candidate. The conclusion of this study is that Oko Mama is a tool for political consolidation in Sgenam Village, but it cannot guarantee that the candidate will obtain the most votes and win the village head election due to educational level and various public perceptions about the candidate. Traditional leaders have power in Saenam Village, but they cannot unite the community if the consolidation tool used is Oko Mama.